1969
DOI: 10.1073/pnas.64.1.316
|View full text |Cite
|
Sign up to set email alerts
|

In vitro DIFFERENTIATION OF A MOUSE NEUROBLASTOMA

Abstract: Abstract. M\Iouse tumor C1300 has been established in tissue culture. The cells have a round cell morphology in both the subcutaneous tumor and in suspension culture. However, when given a surface on which to attach, they send out processes up to 3 mm in length and assume the morphology of mature neurons. The attached cells are stained by the Bodian silver procedure for neurons, whereas the cells grown in suspension are not. Electron microscopy reveals that the attached cells contain neurofilaments, neurotubul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
92
0
1

Year Published

1970
1970
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(94 citation statements)
references
References 10 publications
1
92
0
1
Order By: Relevance
“…Removal of serum from certain neuroblastoma cells induces a low percentage of these cells to sprout neurites and develop a differentiated morphology (Schubert et al, 1969;Seeds et al, 1970). Certain growth factors also stimulate neurite sprouting (Evangelopoulos et al, 2005;Lee et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Removal of serum from certain neuroblastoma cells induces a low percentage of these cells to sprout neurites and develop a differentiated morphology (Schubert et al, 1969;Seeds et al, 1970). Certain growth factors also stimulate neurite sprouting (Evangelopoulos et al, 2005;Lee et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Proliferating cell lines of neuroblastoma express several neuronal characteristics such as process formation (Schubert et al, 1969), neurotransmitter synthesis (Biedler et al, 1978;Pons et al, 1982), high acetylcholinesterase and electrical activities. They lack, however, the ability to synapse between themselves (Zagon et al, 1978) and have a less complex ganglioside pattern than is found for neurons (Stoolmiller, 1973).…”
mentioning
confidence: 99%
“…Despite some abnormalities, due to their neoplastic character, they have proved very useful in the study of formation of neurites, the appearance of enzymes that synthesize neurotransmitters and the acquisition of membrane excitability [15][16][17]. However, if studies on brain maturation have shown large modulations in the various cytoskeletal components, comparable studies 'concerning the neuroblastoma are generally limited to the isotubulins and report moderate changes in their microheterogeneity concomitant with cell differentiation.…”
Section: Introductionmentioning
confidence: 99%